Context Independence and Context Dependence of the Factuality Verb Function In English and Malay Texts - Hashim, Siti Afifah (Pusat Pengajian Ilmu Kemanusiaan, 2019)
As we all know, Malay and English are the two most important languages used in Malaysia. Both are seen as equally important simply because they are extensively used by Malaysians in their daily life; in formal and informal settings. Due to the extensive and frequent use of the languages, it is essential for the users to be fully conversant in both languages to ensure that messages are precisely conveyed with less or no communication breakdown occurs. Much has been said about the differences between English and Malay particularly in terms of the structures and that such difference may have contributed to the inability of the languages users particularly the L2 learners to use the target language effectively (Jalaluddin, Mat Awal & Abu Bakar, 2008). Other similar works have supported this claim (Govindasamy, 1994; Maros, Tan & Salehuddin, 2007; Mohd Ali, 1991). Many other studies claimed that students at secondary and tertiary levels still found it hard to master both languages. This has become a growing concern as it might cause communication breakdowns among the language users or might contribute to the inability to convey messages precisely.